Transcriptome and UPLC-MS/MS reveal mechanisms of amino acid biosynthesis in sweet orange ‘Newhall’ after different rootstocks grafting - Xiong, Bo; Li, Qin; Yao, Junfei; Zheng, Wei; Ou, Yinghong; He, Yuanyuan; Liao, Ling; Wang, Xun; Deng, Honghong; Zhang, Mingfei; Sun, Guochao; He, Siya; et al. (Frontiers in Plant Science, 2023)
Sweet orange 'Newhall' (C. sinensis) is a popular fruit in high demand all over the world. Its peel and pulp are rich in a variety of nutrients and are widely used in catering, medicine, food and other industries. Grafting is commonly practiced in citrus production. Different rootstock types directly affect the fruit quality and nutritional flavor of citrus. However, the studies on citrus metabolites by grafting with different rootstocks are very limited, especially for amino acids (AAs). The preliminary test showed that there were significant differences in total amino acid content of two rootstocks (Poncirus trifoliata (CT) and C. junos Siebold ex Tanaka (CJ)) after grafting, and total amino acid content in the peel was higher than flesh. However, the molecular mechanism affecting amino acid differential accumulation remains unclear. Therefore, this study selected peel as the experimental material to reveal the amino acid components and differential accumulation mechanism of sweet orange 'Newhall' grafted with different rootstocks through combined transcriptome and metabolome analysis. Metabolome analysis identified 110 amino acids (AAs) and their derivatives in sweet orange 'Newhall' peels, with L-valine being the most abundant. L-asparagine was observed to be affected by both developmental periods and rootstock grafting. Weighted gene co-expression network analysis (WGCNA) combined with Redundancy Analysis (RDA) revealed eight hub structural genes and 41 transcription factors (TFs) that significantly influenced amino acid biosynthesis in sweet orange 'Newhall' peels. Our findings further highlight the significance of rootstock selection in enhancing the nutritional value of citrus fruits and might contribute to the development of functional citrus foods and nutritional amino acid supplements.